Weakly binding carbon policy, FDI evolution, and the pollution haven hypothesis: a difference-in-differences analysis of China’s low-carbon pilot cities - Zhang, Chengyue; Jin, Liwei (Frontiers in Environmental Science, 2025)
IndroductionThis study investigates the impact of China’s Low‐Carbon City Pilot (LCCP) policy, characterized by its flexible and “weakly binding” nature, on Foreign Direct Investment (FDI) patterns.MethodsWe specifically focus on the heterogeneous effects of this flexible environmental regulation over time and its micro‐level mechanisms. Employing a quasi-natural experiment framework and a Difference‐in-Differences (DID) methodology, we analyze city‐level panel data and micro‐level enterprise registration data from 2007–2019.ResultsFindings reveal significant temporal heterogeneity: the first LCCP batch (initiated in 2010) suppressed FDI, while the third batch (2017) promoted it. Mechanistically, the initial batch deterred the entry of both polluting and high‐tech foreign firms, whereas the later batch encouraged investment expansion by existing foreign invested enterprises. Furthermore, the policy’s effects are influenced by FDI saturation, resource endowment, and the rigor of policy implementation. Contrary to the Pollution Haven Hypothesis, no significant regional pollution transfer effect was observed; instead, the third batch stimulated positive FDI spillovers in nearby regions (150–200 km).DiscussionThese results provide empirical evidence on how flexible environmental policies shape FDI, offering insights for balancing economic growth and sustainability.